2002
DOI: 10.1046/j.1365-294x.2002.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive exchange of fungal cultivars between sympatric species of fungus‐growing ants

Abstract: Fungal cultivars of fungus-growing ants (Attini, Formicidae) are carried by dispersing queens from parent to offspring nest. This vertical cultivar transmission between generations is thought to result in long-term ant-fungus coevolution and selection for beneficial cultivar traits that maximize harvests and thus colony productivity. In contrast to this traditional view of vertical cultivar transmission, frequent horizontal cultivar transmission between ant species is implicated by a phylogenetic analysis of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
87
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(90 citation statements)
references
References 21 publications
2
87
0
1
Order By: Relevance
“…Each of these fungal cultivars is also employed by other, distantly related attine ants that occupy different microhabitats and that are otherwise quite dissimilar biologically Green et al 2002). Specifically, C. longiscapus shares a narrow group of cultivars of the "Clade 1" type with the sympatric fungus-growing ant Apterostigma auriculatum; molecular data indicate that in one case a cultivar clone has been transferred recently between nests of these two ant species .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these fungal cultivars is also employed by other, distantly related attine ants that occupy different microhabitats and that are otherwise quite dissimilar biologically Green et al 2002). Specifically, C. longiscapus shares a narrow group of cultivars of the "Clade 1" type with the sympatric fungus-growing ant Apterostigma auriculatum; molecular data indicate that in one case a cultivar clone has been transferred recently between nests of these two ant species .…”
Section: Discussionmentioning
confidence: 99%
“…complex; (2) to update the taxonomy of C. longiscapus sensu stricto and to describe the new species; (3) to summarize the morphometrics, distribution, and biology of both species; and (4) to facilitate easy differentiation of these species in the laboratory and the field. The goal of facilitating identification is especially important because, as noted above, C. longiscapus and its relatives are of special biological interest and, as recommended by Mueller and Wcislo (1998), have truly become model organisms in diverse behavioral, ecological, and evolutionary studies Currie et al, 1999Currie et al, a, 1999Villesen et al, 1999;Green et al, 2002;Mueller et al, in press;Villesen et al, in press;Adams et al, unpubl. ;Mehdiabadi and Mueller, unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical work over the past two decades has shown that cultivars are frequently transmitted horizontally between different ant colonies (sometimes between colonies of different ant species) and that lower-attine cultivars are closely related to, and in some cases identical to, free-living fungal species, suggesting frequent import of fungi into the symbiosis from free-living sources [12][13][14]17,21,23,[25][26][27][28][29] . This apparent absence of one-to-one host fidelity (that is, long-term association of ant and fungal genotypes), combined with the recent discovery that the lower-attine fungal Clade 2 ( Fig.…”
mentioning
confidence: 99%
“…Because of the difficulty of obtaining large samples of both ants and fungi from the same nests across the full geographic range of a species, most previous work on the fidelity of association of attine ants and their fungi involved reconstructing phylogenies of fungi but not of their ant hosts, or of ants and fungi drawn from limited localities 12,14,21,26 . A complete understanding of the shared evolutionary history of attine ants and their associated fungi, however, requires detailed understanding of the phylogenies of both interacting partners across their geographic ranges 30 , preferably ant-fungus pairs sampled from the same nests.…”
mentioning
confidence: 99%
See 1 more Smart Citation